Influência da gelatina e pectina na formação de agregados de lecitina e sais de bile - Forster, Júlia da Silva (Universidade Federal de São Carlos, 2025)
Self-aggregated systems formed by biopolymers are highly promising for drug delivery due to their biocompatibility, biodegradability, stabilization capacity and possibility of release control, providing more effective, safe and sustainable treatments. In this study, the formation and characterization of aggregates composed of lecithin/sodium deoxycholate (NaDC) with different proportions (200mM/200mM, 200mM/100mM and 100mM/200mM) and with pectin and gelatin (1%, 3% and 5%) as modulating biopolymers were investigated. The systems were characterized by dynamic light scattering (DLS), zeta potential measurements, rheological analysis and Fourier transform infrared spectroscopy (FTIR). The incorporation of Metronidazole (MDZ) and its evaluation in vertical diffusion cells revealed that the biopolymers significantly altered the system, increasing the repulsive electrostatic interactions between the particles and promoting the formation of aggregates with homogeneous and controlled diameters. Release studies showed that both biopolymers are effective in promoting the sustained release of MDZ, gelatin presenting a fast release profile, while pectin offers a more elastic network, with slower and more controlled release, evidencing the potential of these materials for pharmaceutical applications in drug delivery systems.
Influence of gelatin and pectin on the formation of lecithin aggregates and bile salts
Keywords: Autoagregado; Liberação controlada; Metronidazol; Lecitina; Deoxicolato de sódio; Self-aggregated; Controlled release; Metronidazole; Lecithin; Sodium deoxycholate; CIENCIAS EXATAS E DA TERRA::QUIMICA